Proceedings of the 14th Annual Conference on Genetic and Evolutionary Computation 2012
DOI: 10.1145/2330163.2330276
|View full text |Cite
|
Sign up to set email alerts
|

Tag-based modularity in tree-based genetic programming

Abstract: Several techniques have been developed for allowing genetic programming systems to produce programs that make use of subroutines, macros, and other modular program structures. A recently proposed technique, based on the "tagging" and tag-based retrieval of blocks of code, has been shown to have novel and desirable features, but this was demonstrated only within the context of the PushGP genetic programming system. Following a suggestion in the GECCO-2011 publication on this technique we show here how tag-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Inspired by John Holland's concept of a "tag" ( [11][12][13][14]) as a mechanism for matching, binding, and aggregation, Spector et al [29][30][31] introduced and demonstrated the value of tag-based referencing in the context of GP. In this context, a tag-based reference always links to a tagged entity with its closest match.…”
Section: Tag-based Referencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by John Holland's concept of a "tag" ( [11][12][13][14]) as a mechanism for matching, binding, and aggregation, Spector et al [29][30][31] introduced and demonstrated the value of tag-based referencing in the context of GP. In this context, a tag-based reference always links to a tagged entity with its closest match.…”
Section: Tag-based Referencingmentioning
confidence: 99%
“…functions). SignalGP augments the tag-based referencing techniques demonstrated by Spector et al [29][30][31] to specify which function is triggered by a signal, allowing the relationships between signals and functions to evolve over time. The SignalGP implementation presented here is demonstrated in the context of linear GP, wherein programs are represented as linear sequences of instructions; however, the ideas underpinning SignalGP are generalizable across a variety of genetic programming representations.…”
Section: Introductionmentioning
confidence: 99%
“…On other word, the parse tree is a graphical representation of a derivation which represents the hierarchical structure of the language [15] [17].…”
Section: Parse Treementioning
confidence: 99%
“…To do that, an efficient Context-Free Grammar (CFG), which defines the language, is extremely necessary step. Furthermore, a robust syntactical analysis system to check whether the parser input sentence may generate by a given CFG is also very important step, which requires an efficient Part-Of-Speech (POS) tagging system to assign the syntactic category (noun, verb, and particle) to each word in the input sentence [6] [17]. This paper presents a simple parser to parse Arabic sentences.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by John Holland's use of "tags" (Holland, 1987(Holland, , 1990(Holland, , 1993(Holland, , 2006) as a mechanism for matching, binding, and aggregation, Spector et al (Spector et al, 2011b(Spector et al, ,a, 2012 introduced and demonstrated a tag-based naming scheme for GP where tags are used to name and reference program modules. Tags are evolvable labels that are mutable, and the similarity (or dissimilarity) between any two possible tags is quantifiable.…”
Section: Introductionmentioning
confidence: 99%